2007
DOI: 10.1088/0741-3335/49/11/002
|View full text |Cite
|
Sign up to set email alerts
|

Role of stochastic anisotropy and shear on magnetic field lines diffusion

Abstract: Anisotropy in the magnetic fluctuation spectrum (stochastic anisotropy) and magnetic shear induce variations of global averaged quantities such as the running and the asymptotic diffusion tensors that can be investigated using a semi-analytical method. The study considers ranges for the anisotropy parameter, magnetic Kubo number and shear parameter leading to contrasting dynamical behaviors. In particular, the trapping of the stochastic magnetic field lines is analyzed. An asymptotic 'poloidal' velocity larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
1
22
1
Order By: Relevance
“…Given that both RBD and DD provide inaccurate descriptions of the evolution, and that the ODE provides a transition from RBD to DD behavior, we conclude that all three theories are probably failing due to trapping effects. Some previous studies already concluded that trapping behavior implies that Corrsin's hypothesis does not work properly (Vlad et al 1998;Neuer & Spatschek 2006;Negrea et al 2007), which is a possible explanation for why all these theories are inaccurate for this case.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Given that both RBD and DD provide inaccurate descriptions of the evolution, and that the ODE provides a transition from RBD to DD behavior, we conclude that all three theories are probably failing due to trapping effects. Some previous studies already concluded that trapping behavior implies that Corrsin's hypothesis does not work properly (Vlad et al 1998;Neuer & Spatschek 2006;Negrea et al 2007), which is a possible explanation for why all these theories are inaccurate for this case.…”
Section: Discussionmentioning
confidence: 86%
“…Previous work has often used a closure in terms of Corrsin's independence hypothesis, as described below. (For cases where trapping along flux surfaces is important, an alternative to Corrsin's hypothesis is the decorrelation trajectory method (e.g., Vlad et al 1998;Neuer & Spatschek 2006;Negrea et al 2007). An alternative approach, based on the direct interaction approximation (Kraichnan 1959), has been shown by Vanden Eijnden & Balescu (1995) to be consistent with the present approach.)…”
Section: General Formmentioning
confidence: 99%
“…The simulations and the DCT method yield diffusion coefficients that differ by 50% or less, they can thus be considered to be in good qualitative agreement. Another instance where the results obtained by the DCT method were compared with numerical test-particle simulation, and where also relatively good agreement was found, is given in [33,34].…”
Section: Test-particle Simulationsmentioning
confidence: 96%
“…Note that we can define the vector potential with different normalization factors, such as λ x λ y , λ 2 x or λ 2 y . We have chosen the second case in order to keep the analysis close to the one in [33]. The qualitative results are not changed by the particular choice of the normalization factor.…”
Section: B(x; Z)mentioning
confidence: 99%
“…There is some computational confirmation for the FLRW and analogous problems (e.g., Ottaviani 1992;Reuss & Misguich 1996;Hauff et al 2010). Considerations related to percolation have also been referred to as trapping effects (e.g., Ottaviani 1992;Vlad et al 1998;Neuer & Spatschek 2006;Negrea et al 2007), a term that is broader than percolation. Additional theoretical techniques include the decorrelation trajectory method and A-Langevin equations (Vlad et al 1998;Neuer & Spatschek 2006).…”
Section: Introductionmentioning
confidence: 99%